ESSAY: THE KUNSTWOLLEN OF THE SCIENTIFIC ERA AND ALOIS RIEGL’S STIMMUNG - Vassiliou, Konstantinos (The Nordic Journal of Aesthetics, 2018)
Alois Riegl’s essay “Die Stimmung als Inhalt der modernen Kunst” (1899) has been one of art historiography’s early attempts to bridge art and science. In this text, Riegl not only presents the background of some of his theoretical and methodological premises but he also provides an overarching argument for the way natural sciences af- fect modern spectatorship. In this way, he establishes the basis of a Kunstwollen for the ‘age of the natural sciences’ and describes its appropriate artistic traits. Addressing the intellectual and historical context of the Stimmung Essay, this article shows how Riegl’s ideas work in a subtle and intricate manner, involving the combination of sensual and phenomenological observations to modes of knowl- edge. In this respect, the relation of art and science does not seem to be settled on a fixed contemplative basis but on the combination of the art with cognition and affects.